3D Macroporous Nitrogen-doped Graphene Frameworks for High-Performance Supercapacitors. Issue 1644 (14th March 2014) - Yu, Pingping; Zhao, Xin; Li, Yingzhi; Zhang, Qinghua
ABSTRACT A novel type of nitrogen-doped hierarchically 3D macroporous CMG films electrode (NCMG) was prepared through a facile ultrafiltration method using graphene oxide (GO) and polystyrene (PS) as precursors, then annealed in N2 atmosphere at 1000Â°. This NCMG electrode exhibits high specific capacitance (150 F g-1), excellent rate capacity and good cycle life (98% of initial capacitance), which can be a good candidate for supercapacitor application.